Dehumanist resilience in Tracy Sorensen’s The vitals - O'Brien, Susie (International Journal of English Studies, 2025)
This paper looks to Tracy Sorensen’s 2023 novel, The vitals, to help answer the question: what do we hope for –which bodies, which worlds– when we hope for resilience? The vitals narrates the experience of cancer from the perspective of the author’s abdominal organs and tumours. It is also, less obviously, an intervention into the cultural politics of climate change, informed by Sorensen’s many years as a climate activist. The book also reflects Sorensen’s recognition that climate change, like cancer, represents a challenge to the imagination that is partly attributable to myths of a hierarchical distinction between brain and body and between human and non-human modes of being. This paper reads The vitals as an experiment in dehumanism (Singh, 2018) that counters myths of humanist mastery with an emphasis on place-based imagination, organization and laughter.